IMPLEMENTATION OF LINEAR CONGRUENT METHOD (LCM) ALGORITHM AS A TRAFFICER FOR FAHMIL QUR’AN - Gusti Alfyansyah; Bustami Bustami; Fadlisyah Fadlisyah (TECHSI - Jurnal Teknik Informatika, 2019)
Fahmil Qur'an is one of the branches of the Musabaqah Tilawatil Qur'an (MTQ) race. In the Fahmil Quran race, the participants will be given a package of questions - questions that will be tested by the participants' ability to work together when answering questions given by the jury. And the package of questions that are available is printed poorly, allowing the jury to misrepresent the participants. To avoid repetition in giving questions to participants, a system will be built that is able to randomize the questions automatically. Randomizing the question uses a linear congruent method algorithm. In this research there is a system flowchart and manual calculation of the linear congruent method algorithm.